Challenges experienced by mothers caring for children with cerebral palsy in Zambia - Carol Singogo; Margaret Mweshi; Anthea Rhoda (South African Journal of Physiotherapy, 2015)
Background: Mothers caring for children with disability experience a number of challenges.